KRITIK FILOSOFIS ATAS TUJUAN, VISI, DAN MISI MEMPERTANYAKAN MUTU PENDIDIKAN NASIONAL - Juliansyah Juliansyah (JURNAL LENTERA BISNIS, 2012)
This paper is issuing critics from some academicians, experts, on the topic of objectives, vision, and mission of Indonesian nasional education as stated on UUD Negara Republik Indoneisa 1945 – the country’s constitution, and other Laws about the same topic. This paper’s purpose is to find the different point of view or critics on the topic in order for readers to rethink about the national education objective, vision, and mission. From all critics, we can make the conclusion that the objective, vision, and mission of national education are still not strong. All critics suggest that government or any legal bodies consider about revision on the texts and the application of the regulation about national education. Keywords: objecties, vision, and mission of national education